1992
DOI: 10.1105/tpc.4.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Long regions of homologous DNA are incorporated into the tobacco plastid genome by transformation.

Abstract: We investigated the size of flanking DNA incorporated into the tobacco plastid genome alongside a selectable antibiotic resistance mutation. The results showed that integration of a long uninterrupted region of homologous DNA, rather than of small fragments as previously thought, is the more likely event in plastid transformation of land plants. Transforming plasmid pJS75 contains a 6.2-kb DNA fragment from the inverted repeat region of the tobacco plastid genome. A spectinomycin resistance mutation is encoded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
3

Year Published

1993
1993
2005
2005

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(28 citation statements)
references
References 27 publications
0
25
0
3
Order By: Relevance
“…These authors also found that the transformation frequency in tomato was lower than that obtainable with tobacco. Staub and Maliga (1992) showed that almost all of the 6.2-kb homologous cloned ptDNA in the same ptDNA inverted repeat region as that targeted by pSSH1 integrated in two tobacco plastid transformants. However multiple recombinations were evident when a larger number of transformants were analysed in a homeologous (Solanum/Nicotiana) system with a 7.8-kb target with pSSH1 (Kavanagh et al 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors also found that the transformation frequency in tomato was lower than that obtainable with tobacco. Staub and Maliga (1992) showed that almost all of the 6.2-kb homologous cloned ptDNA in the same ptDNA inverted repeat region as that targeted by pSSH1 integrated in two tobacco plastid transformants. However multiple recombinations were evident when a larger number of transformants were analysed in a homeologous (Solanum/Nicotiana) system with a 7.8-kb target with pSSH1 (Kavanagh et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Selection based on binding-type markers, however, has the advantage that primary transformants are usually homoplasmic, where all plastome copies in cells contain the introduced DNA (Dix and Kavanagh 1995). The bindingtype markers are therefore a good alternative when using PEG-mediated transformation compared to biolistics, given that a large number of shots are needed to recover transformants with these plasmids (Svab et al 1990;Staub and Maliga 1992). An efficient protoplast regeneration system is required irrespective of the selection system used.…”
Section: Introductionmentioning
confidence: 99%
“…The number of plastid genomes per organelle for Arabidopsis seedlings grown under our conditions is not known but is generally estimated to be between 5 and 100 copies per organelle (Herrmann, 1992;Staub and Maliga, 1992). Virtually all of the mitochondrial genes are expressed as monocistronic transcriptional units and do not present very large targets for UV-induced damage.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is feasible to target gene interruptions or deletions to the chloroplast genome of plants (Svab et al, 1990;Staub and Maliga, 1992), such experiments can be performed more quickly and easily with the prokaryotic cyanobacteria. Most cyanobacterial and chloroplast genes show a remarkable degree of sequence homology, and in some cases, the same gene organization has also been reported (Steinmüller et al, 1989;Anderson and Mclntosh, 1991).…”
Section: Introductionmentioning
confidence: 99%